Teacher’s Beliefs and Practices of Authentic Assessment in EFL Speaking Classes: A CASE STUDY - alam, anggit chandra; Abas, Totoh Tauhidin; Saefullah, Hilmansyah (Jurnal Ilmiah Wahana Pendidikan, 2024)
The teacher's obligation to implement authentic assessment has been increasingly emphasized since the publication of the 2013 curriculum. In its implementation, there are still many obstacles faced by teachers, such as the many aspects of assessment and the teacher's lack of understanding of authentic assessment. The focus of this research is to investigate teachers’ beliefs and practices of authentic assessment in assessing students' speaking skills. This study uses a qualitative method with a case study design. The participants in this study were two teachers who had teaching experience of more than 20 years who taught at the same school. Data collection was carried out through interviews and followed by class observations twice a week. The results of this study found that both teachers expressed their beliefs about authentic assessment in terms of authentic assessment concept, assessment reference, authentic assessment task, assessment instrument, and assessment preparation. However, several stated beliefs are not implemented in practice. Based on the findings obtained, the implications in this research indicate the need for guidance to teachers regarding the importance of thorough preparation in assessing students' abilities with established curriculum standards.